A note on stomach contents of minke whales (Balaenoptera acutorostrata) in Icelandic waters - Sigurjónsson, Jóhann; Galan, Anton; Víkingsson, Gísli A (NAMMCO Scientific Publications, 2000)
There is limited available information on food habits of minke whales (Balaenoptera acutorostrata) in coastal Iceland. Sixty-eight minke whales were examined for stomach contents; 51.5% contained fish only, 22.1 % krill (Euphausiacea) only, 25.0% fish and krill together, and one animal (l.5%) had no food remains in the stomach. The fish species identified were capelin (Mallotus villosus), sandeel (Ammodytidae), cod (Gadus morhua) and herring (Clupea harengus). Two species of krill were identified; Thysanoessa raschii and Meganyctiphanes norvegica. Sandeel was the dominant prey species in the western and southwestern areas, while capelin and krill were more frequently found in animals sampled in North Iceland.